2021
DOI: 10.4038/josuk.v14i2.8034
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ion adsorption of <em>Leucaena leucocephala</em> wood biochar activated with coconut vinegar

Abstract: A positive correlation has been reported recently among the number of Chronic Kidney Disease of Unknown Etiology (CKDu) patients and the levels of groundwater hardness.Hence, the need for a low cost and a simple domestic process to reduce the hardness of potable water is identified to improve living standards of low-income communities in these disease affected areas. Biochar has emerged as a low cost adsorbent for water treatment, because of its abundance and cost-effectiveness. This study was aimed to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The experimental adsorption capacity could be greater due to the multilayer physical adsorption. Authors of this study have previously reported the effective use of vinegar-activated biochar in reducing water hardness [11,12]. To our knowledge, no previous studies have reported the adsorption of MB onto Trema orientalis wood biochar or any other form of vinegar-activated biochar.…”
Section: Adsorption Isotherms and Kineticsmentioning
confidence: 82%
See 2 more Smart Citations
“…The experimental adsorption capacity could be greater due to the multilayer physical adsorption. Authors of this study have previously reported the effective use of vinegar-activated biochar in reducing water hardness [11,12]. To our knowledge, no previous studies have reported the adsorption of MB onto Trema orientalis wood biochar or any other form of vinegar-activated biochar.…”
Section: Adsorption Isotherms and Kineticsmentioning
confidence: 82%
“…Nevertheless, these chemicals used in biochar activation are not accessible to rural communities, are unfavoured due to their corrosiveness, need skilled personnel to handle the procedures, and may even cause secondary pollution. Thus, the importance of finding natural activating agents for biochar, which are safe to handle and attainable for rural communities, was identified [11,12].…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation